Maître ou esclave ? Jazz, ragtime et cake walk en Allemagne avant et après la Première Guerre mondiale - Pascale Cohen-Avenel (Amnis)
In 1919, jazz music comes to Germany. This is the beginning of fierce debates over this unheard-of music. Some fear a two-fold dehumanization, linked to the rise of Negro culture and to a kind of modernism gone wild. Others see it, however, as a radical rejuvenation of their own culture; and democrats envision it as a form of mass culture in keeping with the modern metropolis. Yet, in 1919, American rhythm music is not new, since Germans have known about it since 1903. The novelty is rather geopolitical: in 1903, Wilhelm II’s Reich is a major colonial power, whose economic domination is about to outgrow the British Empire. In 1919, however, Germany is defeated, and the new-born Republic has no colonies left. Sarre is occupied by French troops coming from Africa, the economy is decimated, and the Allies give no lee-way to the young democracy to play a part on the international level. This new paradigm explains how intense the debates over jazz music become in the 1920s, as well as their specificities.